The Dynamics of Madurese Words: A Semantic Study on Madurese Kinship Terms - Hikmah, Darul; Rachman, Yudhi (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2025)
Madurese language is one of the major regional languages in Indonesia, with a rich linguistic system that makes it an intriguing area of study. It is an interesting language to study because it has a unique way of expressing meaning. In Madurese, one word can have several different meanings, and eventually different words can mean the same thing. Moreover, when it comes to talking about family relationships in Madurese language, things get even more interesting. The words used by the people in Madura to describe family members can change depending on the situation or who is speaking. On the basis of such issues, this article explores Madurese language with a specific focus on investigating the meaning relations within Madurese kinship terms dealing with three aspects: synonymy, antonymy, and ambiguity. The research aims to explore and classify the various kinship terms in Madurese into these distinct categories. By examining synonymy, antonymy, and ambiguity within Madurese kinship terms, this study seeks to uncover the underlying patterns and relationships that exist among these terms.Accordingly, the research design employed in this study was descriptive qualitative. In addition, to collect necessary research data on the meaning relations within Madurese kinship terms, a combination of observation, depth interviews, and questionnaires was employed. In analyzing the data, an interactive model of data analysis was applied, which includes data reduction, data display, and data verification/claim. The results of this study indicate that the three categories of meaning relations – synonymy, antonymy, and ambiguity – are prevalent within various family relationships in the Madurese community. Those categories of meaning relations exist almost in all Madurese kinship relation system, including in the upward lineages, downward lineage, upward oblique lineage, downward oblique lineage, and lateral lineage.